ANALISIS PERFORMA PESAWAT ATR 72-500 SEBAGAI PESAWAT CHARTER RUTE BANDARA HALIM PERDANAKUSUMA-MATAK DAN HALIM PERDANAKUSUMA- BADAK BONTANG - FORTUNE JR OMBUH; Mufti Arifin; Endah Yuniarti (Jurnal Teknologi Kedirgantaraan, 2023)
With the area and geography of Indonesia consisting of small islands, causing the difficulty of exploration efforts of Natural Resources (SDA) in these small islands. Companies that carry out these exploration activities must build supporting facilities to facilitate the exploration process in the area. The airport is one of the supporting facilities built by the company for exploration activities. The airport built by the company to support this air transportation, must be built according to the land and needs of the company, one of which is the runway. With limited runways, many companies use ATR 72-500 aircraft as charter aircraft to support exploration activities in areas far from commercial airports. Therefore, an analysis of the performance of the ATR 72-500 aircraft as a charter aircraft with the Route Halim Perdanakusuma Airport (HLP) -Matak (MWK) and Halim Perdanakusuma Airport - Badak Bontang (BXT) to determine operational costs. The performance of the ATR72-500 aircraft is seen from the take-off performance needed, range, fuel consumption, and payload. On the route HLP-MWK with 68 passengers traveled with a distance of 577 NM requires fuel as much as 2,456 kg with TOW 22,342 kg, while for take-off requires runway length of 1056 m, operating costs of Rp. 235.535.469, 92 and the cost per passenger is Rp. 3.463.756,91. For the route HLP-BXT with 68 passengers traveled with a distance of 742 NM requires fuel as much as 2.584, 862 kg with TOW 22.471 kg, while for take-off requires runway length of 1068 m, operational costs of Rp. 247.891.620, 16 and the cost per passenger is Rp. 3.645.465.